English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Can u show me the steps to complete this problem

it is suppose to be one of those
equations with variebles on each side

5n + 9 = 2n

2007-01-28 09:15:27 · 6 answers · asked by big boy 1 in Science & Mathematics Mathematics

6 answers

I assume you need to solve for the n-variable, correct?
*Your goal is solving for "n" by isolating it on one side.

First: subtract "2n" from both sides...

5n - 2n + 9 = 2n - 2n

3n + 9 = 0

Sec: subtract "9" from both sides...

3n - 9 + 9 = 0 - 9

3n = - 9

Third: isolate "n" on one side > divide both terms by "3"...

3n/3 = - 9/3

n = - 3

2007-01-28 12:43:28 · answer #1 · answered by ♪♥Annie♥♪ 6 · 0 0

5n + 9 = 2n

Subtract 5n from both sides of the equation

9 = -3n

Divide both sides by a -3 .........that is a negative 3

-3 = n

Do you understand? I tried to make it as simple as possible. Actually you would turn the equation around and place the unknown value on the left side leaving...............................

n = -3


Substituing the answer of -3 into the equation to prove.


5 (-3) + 9 = 2 (-3)

-15 + 9 = -6

-6 = -6

2007-01-28 17:28:19 · answer #2 · answered by James R 5 · 0 0

5n +9=2n
subtract 2n from each side
3n+9=0
subtract 9
3n=-9
divide by 3
n=-3

2007-01-28 17:29:40 · answer #3 · answered by Tom 2 · 0 0

5n + 9 = 2n

3n+9=0 (subtract 2n for both sides)

3n= -9 (subtract 9 for both sides)

n= -3 (divided by 3)

2007-01-28 17:22:16 · answer #4 · answered by      7 · 0 0

5n + 9= 2n
5n-2n+9=0 (subtract 2n from each side)
3n=-9 (combine like terms and subtract 9 from each side)
n=-3 (divide each side by three)

2007-01-28 17:20:32 · answer #5 · answered by moonman 6 · 0 0

5n+9=2n

1st :
5n-2n+9=2n-2n
3n+9=0

2nd :
3n+9-9=0-9
3n= -9

3rd :
n= -3

2007-01-28 17:24:56 · answer #6 · answered by Anonymous · 0 0

fedest.com, questions and answers